2014
DOI: 10.1080/00220272.2014.956796
|View full text |Cite|
|
Sign up to set email alerts
|

Between curriculum complexity and stereotypes: exploring stereotypes of teachers and education in media as a question of structural violence

Abstract: Between curriculum complexity and stereotypes: exploring stereotypes of teachers and education in media as a question of structural violence SILVIA EDLING The paper highlights four tendencies in the media reporting of teachers and education: (a) recurring patterns of defining education in crisis, (b) mantling responsibility as exterior spokespersons for education and teachers, (c) excluding teachers' and educational researchers' knowledge and experiences in the media and (d) simplifying the notion of a good an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…In Australia, Keogh and Garrick (2011) found media discourses contributed towards negative public opinion about teacher quality. In Sweden, Edling (2015) found that the press generally spoke about teachers in over-simplified stereotypes such as the 'good' or 'bad' teacher, ignoring the relational and job complexity of teachers' work. Zemke (2007) found a similar situation in the UK where the press exaggerated the positive and negative aspects of teachers' work.…”
Section: Teachers' Workmentioning
confidence: 99%
“…In Australia, Keogh and Garrick (2011) found media discourses contributed towards negative public opinion about teacher quality. In Sweden, Edling (2015) found that the press generally spoke about teachers in over-simplified stereotypes such as the 'good' or 'bad' teacher, ignoring the relational and job complexity of teachers' work. Zemke (2007) found a similar situation in the UK where the press exaggerated the positive and negative aspects of teachers' work.…”
Section: Teachers' Workmentioning
confidence: 99%
“…Negative discourses about professional teachers and their performance are repeatedly, but not always, reported by actors external to education and within the media (Edling, 2015;Mockler, 2020). These negative discourses are problematised by the media as viewing education in a permanent state of crisis; as acting as spokesperson for teachers but excluding teachers'/educators'/educational researchers' knowledge and experiences and stereotyping the 'good teacher' while overlooking the task and relational complexities that go along with the roles (Edling, 2015). Media in this instance refers to various channels through which public information is 1 At the outset and as caveat the authors are not taking the stance that all teachers are perfect; in addition, the authors acknowledge that media commentary is often politically motivated by interests separate from education and its stakeholders.…”
Section: Negative Discourses and The Mediamentioning
confidence: 99%
“…Negative discourses about professional teachers and their performance are repeatedly, but not always, reported by actors external to education and within the media (Edling, 2015 ; Mockler, 2020 ). These negative discourses are problematised by the media as viewing education in a permanent state of crisis; as acting as spokesperson for teachers but excluding teachers’/educators’/educational researchers’ knowledge and experiences and stereotyping the ‘good teacher’ while overlooking the task and relational complexities that go along with the roles (Edling, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, in the education context, teachers are most often portrayed as unknowing, unempowered, and lacking in both the knowledge and the resources to do their job well (e.g., Edling, 2015). On the other hand, many (but not all) popular trade books about reading are written by men who are cognitive scientists with no classroom experience or experience researching in classrooms.…”
Section: Authority and Expertisementioning
confidence: 99%